Optimization of The Physical Properties of Gas Fluids At the Stage of Field Exploitation Activity At Gas Field "X" - Julianto, Cahyadi; Priambodo, Aldi; Tulloh, Hidayat; Nugroho, Muhammad Rizky (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Gas Field “X” is field gas located on Prabumulih, South Sumatra. The “X” Field consist of 12 active well which produce gas from the BRF Layer (Baturaja Formation). After calculating the gas reserves of field “X”, Original Oil In Place (OGIP) is 526.48 BSCF. The purpose of optimization of the physical properties of gas fluids is to know the characteristics of gas fluids at the exploitation stage of the “X” gas field. From the gas composition, we know that the properties of gas from the field “X” dominated by methane, and the composition of impurities not so high. So, to know the fluid characteristic of reservoir required calculation with some correlation. If the characteristics of the gas fluid are known then it can calculate the welltest value, recovery factor value, and design of the surface gas production facilities. The methodology used to determine the physical fluid properties of gas at field “X” is to perform calculations on the physical fluid gas properties : Z factor, using Beggs And Brill correlation by consider the Pseudocritical Pressure (Ppc), Viscosity using Carr correlation, also viscosity of gas impurities (N2, CO2, and H2S), and Gas Formation Volume Factor (Bg) using Real gas equation-of-state correlation. Calculation of parameters, and analysis of PVT data conducted using Well X-01 as a research object. The results of PVT data analysis is considered to represent the real condition of BatuRaja Formation of Reservoir Gas Field "X". From the calculation, the value of physical properties obtained is Z factor of 0.804061 with Pseudocritical Pressure (Ppc) of 747,014 Psi, viscosity of 0.017115cp with N2 correction for gas viscosity of 0.000008, CO2 correction for gas viscosity of 0.001071, H2S correction for gas viscosity of 0. In addition, the value of the Gas Formation Volume Factor (Bg) is 0.00084 cuft/scf. These parameters are calculated at the same pressure value, then the fluid characteristics of the reservoir can be known at each pressure drop assuming the isothermal condition of reservoir.